2014
DOI: 10.2355/isijinternational.54.1755
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al Content on the Characteristics of Inclusions in Al–Ti Complex Deoxidized Steel with Calcium Treatment

Abstract: To improve the effect of calcium treatment and the cleanliness of steel and to make use of fine TiOx to refine the microstructure of steel, the effect of aluminum content on inclusion characteristics of aluminum-titanium complex deoxidized and calcium treated steel is investigated based on the experiment with SEM/EDS, Image Pro-Plus 6.0 and FactSage 6.1 softwares and thermodynamic calculation in the present work. The results show that the inclusions in two steels with different aluminum content are obviously s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 34 publications
5
21
0
Order By: Relevance
“…It is noticeable that the stability region of liquid calcium aluminate is located in a common calcium content range. As the compositions of the steel samples in the current work (based on the content of the calcium and titanium) and experimental results introduced from Seo and Zheng [38,39] were marked in the phase diagrams, a good consistency in the above data is conspicuous, as shown in Figure 6b,c. Consequently, the calculated phase diagrams of Al-Ca-Ti-O system are reliable for effectively estimating the evolution behavior of inclusions at steelmaking temperature.…”
Section: Thermodynamic Analysis Of Al-ti-ca-o Systemsupporting
confidence: 73%
See 1 more Smart Citation
“…It is noticeable that the stability region of liquid calcium aluminate is located in a common calcium content range. As the compositions of the steel samples in the current work (based on the content of the calcium and titanium) and experimental results introduced from Seo and Zheng [38,39] were marked in the phase diagrams, a good consistency in the above data is conspicuous, as shown in Figure 6b,c. Consequently, the calculated phase diagrams of Al-Ca-Ti-O system are reliable for effectively estimating the evolution behavior of inclusions at steelmaking temperature.…”
Section: Thermodynamic Analysis Of Al-ti-ca-o Systemsupporting
confidence: 73%
“…It is generally the technique of calcium treatment that has been introduced to get liquid phases of calcium aluminate at casting temperature, which relieves the nozzle clogging issue during continuous process of steels, especially of grades of Al-killed steel, and also has benefits for the mechanical performance of final steel products [27][28][29][30][31][32][33][34][35][36][37]. However, the research involving the calcium treatment process of Ti-bearing Al-killed steel have been limited, until now [38][39][40][41][42]. In addition, the types of inclusions at the solidification temperature are directly related to the properties of the inclusions in the final product.…”
Section: Introductionmentioning
confidence: 99%
“…7. It can be easily seen that the equilibrium relation calculation in the present work shows a good agreement with the experimental data of Seo et al, 33) Zheng et al, 34) Kimura et al 63) and Inoue et al 64) in the previous work. Therefore, Al-Ti-Ca-O phase diagram can be used to evaluate the change process of oxide inclusion effectively.…”
Section: Thermodynamic Calculation Of Al-ti-ca-o Complex Inclusionssupporting
confidence: 80%
“…[25][26][27][28][29][30][31][32] However, few systematic reports have been published on the deoxidization, especially inclusion evolution by calcium and titanium complex treatment yet. [33][34][35] Besides, the evolution process and phase stability of the inclusions in the melts are not clarified due to lack of exact thermodynamic calculation. Thus, it is of interest to explore the formation and evolution of Al-Ti-Ca-O complex inclusions in detail.…”
Section: Introductionmentioning
confidence: 99%
“…And the growth rate of MnS was determined by the diffusion of manganese and sulphur in the liquid steel. Zheng et al 6) found that not only the precipitation rate but also the thickness of MnS on the oxides increased with the increase of sulphur concentration…”
Section: Introductionmentioning
confidence: 99%